Letter from Paddington Central Strike Committee (NUR) to General Council, 5 May 1926, Re: Need for strike bulletin
1926-05-05 "Letter from Paddington Central Strike Committee (NUR) to General Council, 5 May 1926, Re: Need for strike bulletin" [g0725001.jpg], 5 May 1926, National Union of Railwaymen TUC Organisation